2011
DOI: 10.1021/jp202804g
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Study of Functionality Impact on Sodalite–Zeolitic Imidazolate Frameworks for CO2Separation

Abstract: This study deals with the enhancement of CO 2 uptake by ligand functionalization of zeolitic imidazolate framework (ZIF) materials. The ligand dipole moment could be considered as one of the main criteria for CO 2 adsorption enhancement. To verify this hypothesis, an experimentalÀ computational study was performed on an isoreticular ZIF series with sodalite (SOD) topology using published structures (ZIF-8, ZIF-90, and ZIF-Cl) as well as hypothetical structures (ZIF-COOH and ZIF-NO 2 ) designated using DFT calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
151
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(166 citation statements)
references
References 50 publications
15
151
0
Order By: Relevance
“…However, at high pressures (≥ 1bar) the agreement between simulation results and experimental data is good. Besides, a further comparison was made between the simulated results obtained in this work and the results reported by Amrouche et al (2011) at high pressures, and the agreement was also good. Moreover, in this work CO 2 solubility in the IL and ZIFs mixed separating agent was measured at temperatures from 243.2 to 298.2 K and pressures from 4.0 to 30.0 bar.…”
Section: Gcmc Simulation For Adsorption Of Co 2 With Zifssupporting
confidence: 64%
“…However, at high pressures (≥ 1bar) the agreement between simulation results and experimental data is good. Besides, a further comparison was made between the simulated results obtained in this work and the results reported by Amrouche et al (2011) at high pressures, and the agreement was also good. Moreover, in this work CO 2 solubility in the IL and ZIFs mixed separating agent was measured at temperatures from 243.2 to 298.2 K and pressures from 4.0 to 30.0 bar.…”
Section: Gcmc Simulation For Adsorption Of Co 2 With Zifssupporting
confidence: 64%
“…67 A recent study on ZIFs showed that there is a very good agreement between isotherms computed from DFT optimized structures and isotherms from the XRD structures. 35 The idea of our calculations is that, once the potential value of a material has been demonstrated using molecular simulations, a more detailed calculation approach including framework flexibility can be used to increase the precision of the assessment. Our calculations do not provide any information about the stability of the materials.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years a great number of studies have demonstrated the unique potential of Metal-Organic Framework (MOF) [8][9][10][11][12][13][14] [15] and Zeolite Imidazolate Framework (ZIF) [16][17][18][19] materials for the adsorption and separation of CO, CO 2 , CH 4 and H 2 gases, due to their extremely high porosity [20], characterised by large surface areas and pore diameters [21]. In conjunction with experimental techniques, the use of simulation in modelling the adsorption properties of MOFs [8,[22][23][24][25][26] and ZIFs [27][28][29] has been increasingly established as a powerful tool in the design of new materials with enhanced affinity and selectivity for CO 2 .…”
Section: Introductionmentioning
confidence: 99%